Mitogenomics of macaques (Macaca) across Wallace's Line in the context of modern human dispersals. Issue 146 (September 2020) - Evans, Ben J.; Gansauge, Marie-Theres; Tocheri, Matthew W.; Schillaci, Michael A.; Sutikna, Thomas; Jatmiko,; Saptomo, E. Wahyu; Klegarth, Amy; Tosi, Anthony J.; Melnick, Don J.; Meyer, Matthias
Abstract: Wallace's Line demarcates a biogeographical boundary between the Indomalaya and Australasian ecoregions. Most placental mammalian genera, for example, occur to the west of this line, whereas most marsupial genera occur to the east. However, macaque monkeys are unusual because they naturally occur on both western and eastern sides. To further explore this anomalous distribution, we analyzed 222 mitochondrial genomes from ∼20 macaque species, including new genomes from 60 specimens. These comprise a population sampling of most Sulawesi macaques, Macaca fascicularis (long-tailed macaques) specimens that were collected by Alfred R. Wallace and specimens that were recovered during archaeological excavations at Liang Bua, a cave on the Indonesian island of Flores. In M. fascicularis, three mitochondrial lineages span the southernmost portion of Wallace's Line between Bali and Lombok, and divergences within these lineages are contemporaneous with, and possibly mediated by, past dispersals of modern human populations. Near the central portion of Wallace's Line between Borneo and Sulawesi, a more ancient dispersal of macaques from mainland Asia to Sulawesi preceded modern human colonization, which was followed by rapid dispersal of matrilines and was subsequently influenced by recent interspecies hybridization. In contrast to previous studies, we find no strong signal of recombination in most macaque mitochondrial genomes. These findings further characterize macaque evolution before and after modern human dispersal throughout Southeast Asia and point to possible effects on biodiversity of ancient human cultural diasporas.